Meningkatkan Kemampuan Penjumlahan dengan Media Counting Stick pada Anak Disabilitas Intelektual Ringan - Mardison, Mardison; Mahdi, Arisul; Budi, Setia; Arnez, Gaby (Indo-MathEdu Intellectuals Journal, 2026)
Students with mild intellectual disabilities experience difficulties in understanding abstract mathematical concepts, particularly basic addition skills involving numbers 1–10. A preliminary study at SLB Al-Ishlaah Padang revealed that a fifth-grade student still had difficulty performing addition despite using simple concrete media, resulting in inaccurate responses. This study aimed to improve addition skills for numbers 1–10 through the use of counting stick media. The research employed a Single Subject Research (SSR) method with an A–B design consisting of a baseline phase and an intervention phase. The research subject was a fifth-grade student with a mild intellectual disability. Data were collected through observation, addition tests, interviews, and documentation, and analyzed using descriptive quantitative techniques by comparing performance before and after the intervention. The results showed that the student’s addition skills during the baseline phase were low, while a significant and consistent improvement was observed during the intervention phase. These findings indicate that counting stick media are effective in improving basic addition skills for students with mild intellectual disabilities.